2006
DOI: 10.1080/00016340500410024
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic girdle pain in pregnancy: The impact on function

Abstract: Pain related to the pelvic joints is common among pregnant women in Norway and may cause serious functional problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
2
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 18 publications
7
87
2
3
Order By: Relevance
“…This subgroup has been associated with greater functional disability, more frequent sick leave, and significantly worse prognosis than pain in one or two pelvic locations. 2,3,28 Furthermore, it has previously been shown that the number of pain sites has a strong predictor utility. 9 This strengthens our classification of severity level during pregnancy, which was based on pain intensity, pain location, and the number of pain sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This subgroup has been associated with greater functional disability, more frequent sick leave, and significantly worse prognosis than pain in one or two pelvic locations. 2,3,28 Furthermore, it has previously been shown that the number of pain sites has a strong predictor utility. 9 This strengthens our classification of severity level during pregnancy, which was based on pain intensity, pain location, and the number of pain sites.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Hence, it should be regarded as a major women's health issue. The reported recovery rates after delivery are high.…”
Section: Introductionmentioning
confidence: 99%
“…Both low back pain (LBP) and pelvic girdle pain (PGP) develop in many women during pregnancy [3,22,25]. In a smaller fraction, the pain persists for years after childbirth [14,23].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies concluded that level and onset of pain during pregnancy were strong predictors for persistent lumbopelvic pain [20,29]. Prepregnancy back pain and severity of complaints were also found to play a prognostic role in the study of Röst and co-workers [26], whereas a retrospective study found no association between previous back pain and PGP [25]. One study indicates that pain location might be important [1].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this musculoskeletal disorder is responsible for high levels of sick leave and financial cost [2]. Studies report PPGP and low back pain account for one-third of sick leave in the Scandinavian countries [3][4][5]. Interestingly, PPGP is not influenced by economic or cultural differences when comparing different countries [6].…”
Section: Introductionmentioning
confidence: 99%